2023
DOI: 10.3389/fnut.2023.1150789
|View full text |Cite
|
Sign up to set email alerts
|

Food neophobia and its association with dietary choices and willingness to eat insects

Abstract: Growing populations, changing dietary preferences and limitations on natural resources have meant that finding an alternative to traditional animal-based protein sources is a priority. Insects have been proposed as a possible solution due to their many benefits including low resource inputs and rich nutritional profile. However, insects are not consumed on a large scale by Australians. Food neophobia (reluctance to try new foods) could be contributing to this delay and as such, this study aimed to explore the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…Insects differ in taste, shape, use, maturity stage, and serving form. The most significant barrier in Western countries is the lack of taste acceptance and a high level of neophobia, often resulting from prejudices and a lack of knowledge [20][21][22]. On the other hand, these countries have a strong awareness of taking care of the planet and the environment, so it is suggested that acting for higher goals might be an impetus to introduce insects into daily diets.…”
Section: Introductionmentioning
confidence: 99%
“…Insects differ in taste, shape, use, maturity stage, and serving form. The most significant barrier in Western countries is the lack of taste acceptance and a high level of neophobia, often resulting from prejudices and a lack of knowledge [20][21][22]. On the other hand, these countries have a strong awareness of taking care of the planet and the environment, so it is suggested that acting for higher goals might be an impetus to introduce insects into daily diets.…”
Section: Introductionmentioning
confidence: 99%
“…Simulation results of the IOT application in smart agriculture system. Table6presents the comparison between the previous results[2][3][4] and the current results.…”
mentioning
confidence: 89%
“…Observations from inflow Equation (3) show that the time constant depends on the resistance (pipe opening) of the outlet pipe and the cross-sectional area.…”
Section: 𝑓 = 𝑅𝜌𝑔ℎmentioning
confidence: 99%
See 1 more Smart Citation
“…This aversion is influenced by individual traits, cultural aspects, and socioeconomic conditions, which can restrict exposure to unfamiliar foods [21,22]. Obstacles such as unfamiliarity, sensory variations, and inherent disgust and fear of new things present significant challenges to achieving broader acceptance of edible insects [23,24]. Despite the reluctance of many consumers towards this type of new food, market research indicates an increase in the number of producers and consumers.…”
Section: Introductionmentioning
confidence: 99%